Free Riding Problem: Perspectives and Solutions - Ram Kumar Dwivedi, Shivang Rampriyan, Dr. Ankit Saxena, Dr. Arun Koushal, Himani Oberoi, Shivam Bharadwaj (International Journal of Advanced Science and Technology, 2020)
Non-excludability is a defining feature of public goods. This makes it expensive to restrict their access to a specific section of the population, which encourages many users of these goods to shirk off their responsibility of paying for the benefits they receive at the expense of the others, who pay. Due to these behaviors, most studies on the above-mentioned free riding problem have been focused on understanding free riding in an economic perspective. In this paper, we first define the free riding problem from a market perspective and highlight its core elements using a similar approach. Then we try to frame the concept of free riding in an institutional perspective and analyze it using the concept of prisoners’ dilemma, adopting mathematical approach of the game theory. Moving ahead, we also describe free riding through its associated moral hazard, while simultaneously invoking multiple theories on ethics to provide justifiable explanations and solutions to the observed behaviors of free-riders. Throughout the paper, we have tried to support our reasoning through logical deductions from hypothetical case studies, which enabled us to arrive at conclusions which will explain the observations. Had we not analyzed the free riding problem from a lens of multiple socioeconomic perspectives, it would have been difficult to exhaustively explain the results of the cases. Towards the end of the article, we involve concepts from a fairly recent branch of study in social sciences, viz., Political Economy. This opened up newer vistas providing a fresher gaze on the free riding problem under the realm of capitalism, welfare and environmental justice. We conclude by providing constructive insights on the behaviors of free-riders and summarizing the various solutions inferred throughout the text.